Caveolins; An Assailant or An Ally of Various Cellular Disorders - Srivastav, Ritesh Kumar; Ansari, Tarique Mahmood; Prasad, Mahesh; Vishwakarma, Vishal Kumar; Bagga, Paramdeep; Ahsan, Farogh (Drug Research, 2019)
Caveolae have impressive morphological highlights of the cytomembrane of mammalian cells which involve in wide diversity of cellular functions involving signaling pathways and cholesterol hastening. Caveolin proteins possess a ‘scaffolding’ domain which for caveolin-1 and caveolin-3 appear to act a dominant role in signal regulation through caveolae. Caveolin-1 is treated to be protein in the cytomembrane entrapped with caveolae in endothelial cells and vascular smooth muscle cells which diminish nitric oxide (NO) by fill up the calcium/calmodulin (Ca2+/CaM) confining point of endothelial nitric oxide synthase (eNOS), decrease NO generation produce endothelial dysfunction and atherosclerotic injury development. It is a cholesterol-binding layer protein associated with cell cholesterol transport and also shows cardioprotective action through ischemic preconditioning (IPC) in diabetic and postmenopausal rat heart. Additionally it is ensnared in the procedures of tumorigenesis, prostate disease, and inflammation. The present study in the paper is to explore the structural functionalities of caveolins and their contributory role in CVS disorders and various other diseases.
Keywords: caveolins; cardiovascular disorder; diabetic; ischaemic preconditioning; nitric oxide; cell growth